Android wireless application development - Conder, Shane, 1975- (Addison-Wesley Professional, 2009)
The start-to-finish guide to Android development-from concept to market! Android Wireless Application Development combines all the reliable information, sample code, and best practices you need to build, distribute, and market successful Android mobile applications. Drawing on their extensive experience with mobile and wireless development, Shane Conder and Lauren Darcey cover everything you need to execute a successful Android project: from concept and design through coding, testing, packaging, and delivery. Conder and Darcey explain how mobile development differs from conventional development, how Android differs from other mobile platforms, and how to take full advantage of Android's unique features and capabilities. They present detailed, code-rich coverage of Android's most important APIs, expert techniques for organizing development teams and managing Android projects, and dozens of time-saving tricks and pitfalls to avoid. Master the latest Android development tools and Android SDK 1.5 Use the Eclipse Development Environment for Java to develop and debug Android applications Design Android applications that are more efficient, reliable, and easier to use and offer better performance Work with Android's optional hardware-specific APIs Use Android's APIs for data, storage, networking, telephony, Location-Based Services (LBS), multimedia, and 3D graphics Leverage advanced Android capabilities such as Notifications and Services Ensure quality through solid test planning, efficient testing, and comprehensive defect tracking Make more money from your Android applications This book is an indispensable resource for every member of the Android development team: software developers with all levels of mobile experience, team leaders and project managers, testers and QA specialists, software architects, and even marketers.